The Constitutional Interpretation of Constitutional Court Decision Number 128/PUU-XXIII/2025 Regarding The Prohibition of Ministers and Deputy Ministers Holding Multiple Positions in Indonesia - Wasil Haqqullah, Moh. (JURNAL SULTAN: Riset Hukum Tata Negara, 2025)
Indonesia is a country that adopts a presidential system of government. In this system, an elected President is assisted by Ministers and Deputy Ministers in carrying out state duties. This is affirmed in the 1945 Constitution of the Republic of Indonesia, Article 17, paragraphs (1) to (3). However, the problem with these Ministers and Deputy Ministers in the current government is that 32 Ministers and Deputy Ministers hold dual positions in state-owned enterprises and other institutions, such as political parties. The prohibition on dual office-holding for Ministers and Deputy Ministers is regulated by Law No. 39 of 2008 concerning State Ministries, Article 23, which explicitly prohibits Ministers from holding dual office. This is further addressed in the Constitutional Court Decision Number 128/PUU-XXIII/2025 regarding the prohibition on dual office-holding for Ministers and Deputy Ministers. Based on the background of the problem, the author formulates the research question: How can the principles of good governance of state institutions be realized? What are the constitutional losses for civil society regarding Ministers and Deputy Ministers who hold dual positions in SOEs and Political Parties? What is the ratio decidendi of the Constitutional Court Justices regarding Decision No. 128/PUU-XIII/2025? This type of research uses normative research, and the research approaches are the statute approach and the case approach. The results of this study indicate that conflicts of interest arising from ministers and deputy ministers holding multiple positions will lead to abuse of power, thereby negatively impacting good governance. Dual office-holding often leads to conflicts of interest between the positions of Minister and Deputy Minister and structural positions in state-owned enterprises and political parties. Thus, this phenomenon of dual office-holding will affect performance in the duties and functions of each ministry, and will not comply with applicable laws and regulations.